The Manuscript from Afterlife. Jakub Deml’s The Castle of Death - Pająk, Patrycjusz (Poznańskie Studia Slawistyczne, 2013)
In the story The Castle of Death(1912) Jakub Deml presents an esoteric text, which allows initiation, that is to say the revival and improvement of human spirit, because it points the way to the absolute hidden behind the words. The highest form of initiation is transcendence, which consists in the unity of life and death. To achieve this, the candidate of initiation must die in this world. Deml shows the horror of death by the conventions of a horror story. In The Castle of Death, writing and reading the esoteric text means the confrontation between the life-giving language and the ineffable silence of death. This confrontation leads to the acceptance of silence, because in the world of absolute language as the medium of the spirit loses its raison d’être. To emphasize the uniqueness of esoteric text, Deml uses the form of a found manuscript. He presents the moment of transition between temporality and transcendence as a dream that goes back to a source of human life.